The History of the Latin-graphic Book of Psalms in the Church Slavonic Language from Norov´s Book Collection - Celunova, Jelena (Slavistica Vilnensis, 2022)
This article is devoted to the research of the History of the Book of Psalms manuscript from A.S.Norovʼs book collection stored in the Department of manuscripts of the Russian State Library. The manuscript was written at the beginning of the 18th century in Church Slavonic language Polish letters by two nuns from the East Slavic region of the Polish-Lithuanian Commonwealth who moved to Russia at that time. Very few such texts have survived, and almost all of them were created in the Polish-Lithuanian Commonwealth. Records by the owners of the manuscript indicate that the manuscript was found at the estate of Prince Andrei Dolgorukov near Moscow — in the village of Bogorodskoye located in the immediate vicinity of the Moscow Ascension maiden Monastery. It is suggested that the creator of the manuscript could be a village nun of this monastery who lived in the village of Bogorodskoye. The article analyzes indirect information about the authors of the manuscript and draws a conclusion about their use of certain symbols characteristic of the cultural and theological environment of the Polish-Lithuanian Commonwealth.